Searching skills of fourth year UP Diliman BLIS students - Barro, Jesseca B.; Lapuz, Elvira B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
In this internet-powered society where information overload and easy accessibility of abundant information exist, information literacy skills are more important than ever. One of the information literacy skills is searching skill. By having the necessary searching skills, you can locate and find the relevant information you need, use it properly and can relate it to an existing knowledge base easily. This study intended to gain a better understanding of the searching skills of fourth year Bachelor of Library and Information Science (BLIS) students at the School of Library and Information Studies of the University of the Philippines Diliman. This study also intended to find out the selected information resources/services the students' used when searching for information, search methods used when searching on print materials, the internet, and the reliability of the information sources, search strategies used when searching the library databases and search engines for information, and the factors that could affect the searching skills. Out of the 69 fourth year BLIS students with graduating status as of second semester of school year 2008-2009, only 62 responded.
From the data gathered, majority of the students frequently used the internet search engines and online reference materials compared to the other information sources/services since these information sources are accessible anywhere with an internet connection and searching for information is faster. The search methods that majority of the students used are searching for the index of printed materials to look for list of subjects, names, titles, etc. that could help them locate the information they need, using the search engines when searching information online, and assessing the relevance of information they find by examining elements of the citation of the information sources such as title, abstract, subject headings, sources and date of publication. Majority of the students are familiar with and use the basic search strategies rather than the advance search strategies when searching the library databases and search engines. There are many factors that could affect the searching skills of the fourth year U.P. Diliman BLIS students. The factors that affected the searching skills of the students most were their change of interest and the subjects LIS 71 and LIS 64 that helped develop the students' searching skills. Majority of the fourth year U.P. Diliman BLIS students rated their searching skills as 7 from scale 0 to 10. The rate 7 and 8 got the two highest frequencies which show that students are good in some aspects of their searching skills but there is still a need to develop some area of their skills. "
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines School of Library and Information Studies -- Students; Ability; Internet searching; Searching, bibliographical